The Effect of Concentrations Bioherbicide Kirinyuh Leaf Extract to Control The Growth of Teki Weeds - Nudin, Fatwa; Nurmayulis, Nurmayulis; Yenny, Ratna Fitry; Putri, Widia Eka (Jurnal Biologi Tropis, 2024)
The research was aimed to know the effect of different concentrations bioherbicide of kirinyuh leaf extract to control the growth of teki weeds. This research was conducted from Juny until August 2024 in Sindang Resmi, Purwaraja village, Menes district, Pandeglang city, Banten and Biotechnology Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University. The method used Randomized Completely Block Design with one factor. The factor with five replications to obtain 25 experimental units, namely: 25%, 50%, 60%, 75% and 90% . The results showed that kirinyuh leaf extract 90% has a significant effect for plant height at 5 days after planting (DAP) (4.40 cm), 10 DAP (13.40 cm), 20 DAP (21.60 cm), 25 DAP (26.60 cm) and 30 DAP (27.80 cm). Plant dry weight (6.00 g) and crown dry weight (3.20 g). The treatment of different consentrations of kirinyuh leaf extract showed significant differences on the parameters.